3-Formylindole-4-aminobenzoic Acid: A Potential Corrosion Inhibitor for Mild Steel and Copper in Hydrochloric Acid Media. (26th November 2012) - Paul, Aby; Thomas K., Joby; Raphael, Vinod P.; Shaju, K. S.
Abstract : The corrosion inhibition efficiencies of Schiff base 3-formylindole-4-aminobenzoic acid (3FI4ABA) on mild steel (MS) and copper in 1.0 M HCl solution have been investigated using weight loss measurements, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization studies. The results show that inhibition efficiencies on both metals increase with increasing the concentration of the inhibitor. 3FI4ABA exhibited comparatively good inhibition towards mild steel in HCl medium even at low concentrations. The adsorption of inhibitor on the surfaces of the corroding metal mild steel and copper obeys the Langmuir isotherm. Polarization studies revealed that 3FI4ABA acts as a mixed-type inhibitor. Thermodynamic parameters (K ads, Δ G ads 0 ) were calculated using the Langmuir adsorption isotherm.